In vivo study of antipyretic activity of Sampare leaf extract (Glochidion sp.) from Biak-Numfor Regency - Nur F. Bakri; Artha M. Simanjuntak; Mustika E. Pratiwi; Agatha C.I. Jedaut; Napita P.C. Pasaribu; Felycitae E. Appa (Jurnal Biologi Papua, 2026)
The local people of Biak Regency use the Sampare Leaf (Glochidion sp.) to cure malaria and reliefe fever. This plant contains flavonoid compounds, alkaloids, saponins, and tannins that can act as antipyretics. This study aims to determine the antipyretic activity and the most effective dosage of Sampare leaf extract as an antipyretic. The research method was a laboratory experimental. The antipyretic testing method used is peptone-induced fever. A total of 30 mice were divided into 6 treatment groups. The inducing solution, peptone, is induced subcutaneously, and the test solution is administered orally. The results showed that Sampare leaf extract had a percent antipyretic power, namely at 150mg/kgBW of 30.17%, a dose of 200mg/kgBW of 49.66%, and a dose of 250mg/kgBW of 70.80%. The ANOVA test showed that the 250mg/kgBW extract treatment group and the 200mg/kgBW dose with the positive control group has no significant difference, so it can be concluded that the 250mg/kgBW extract dose is an effective dose that provides a good antipyretic effect.